If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2m = m + -3 Reorder the terms: 6 + -2m = -3 + m Solving 6 + -2m = -3 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 6 + -2m + -1m = -3 + m + -1m Combine like terms: -2m + -1m = -3m 6 + -3m = -3 + m + -1m Combine like terms: m + -1m = 0 6 + -3m = -3 + 0 6 + -3m = -3 Add '-6' to each side of the equation. 6 + -6 + -3m = -3 + -6 Combine like terms: 6 + -6 = 0 0 + -3m = -3 + -6 -3m = -3 + -6 Combine like terms: -3 + -6 = -9 -3m = -9 Divide each side by '-3'. m = 3 Simplifying m = 3
| 9-7x=-4x+21 | | 2/3+a=-1/3 | | 5(1-2x)=-11(x-2) | | 10b=2b-16 | | -5c=5/24 | | 3x-6=3-6x | | 8b=5b-9 | | 2/3+4/15 | | -2(n-8)=-4(-1-n) | | -7x-4y=28/-4 | | x-(-2/3)=2/3 | | 6-7x=-5x-2 | | 6xa=5 | | x/4.4=-15.6 | | 10x=5/12 | | 2x+1/5x+3 | | 3(2b+6a)=4b-8 | | 9(42-3)=9x+15 | | 2x=8y+24 | | x/4+3 | | 6x+2=3x-34 | | t/6.8=-0.2 | | 9b=2b+7 | | g/3+15=26 | | 10-x=5x+10 | | 6/11w=-1/5 | | 10=5/3/4 | | 3/2=n+2 | | 4x-8=8(1+x) | | (-3i+4j-5k)*(3i-4j+5k)= | | -18x+8y=3 | | -2=2x^2-12x |